Post-evaluation model for 500 kV substation engineering projects using the fuzzy comprehensive evaluation method - Jianquan Chen; Yi Zhuang; Shaoyong Chen; Zhongtian Zhang; Yu Zhang (Heliyon)
To accurately assess the economic benefits and expected outcomes of investing in a 500 kV power transmission and substation project, it is essential to conduct a comprehensive economic evaluation of the entire system. This paper develops a post-evaluation model based on the fuzzy comprehensive evaluation (FCE) method tailored for 500 kV transmission and substation projects. Using this model, the implementation process is thoroughly evaluated. First, the analytic hierarchy process is employed to determine the weights of each evaluation indicator, taking into account factors such as planning effectiveness, preliminary achievements, bid management efficiency, construction performance, project outcomes and benefits, social and environmental impacts, and project sustainability. Next, tailored scoring criteria are established based on practical circumstances, categorizing indicators into qualitative and quantitative types. Through the FCE method, qualitative indicators are converted into quantitative data, with expert opinions aggregated using the Delphi method to derive the final evaluation results. Quantitative analysis across multiple indicators yields an overall project success score of 92.54, reflecting outstanding performance in areas such as planning effectiveness (100.00), preliminary achievements (99.12), and construction performance (98.00). Furthermore, both social and environmental impact scores are perfect (100.00), underscoring the project's positive contributions to regional economic and social development. However, the economic benefit indicator scores only 61.88, particularly with a financial performance score of 54.33, highlighting areas for improvement in cost control and fund utilization. Based on these findings, this paper proposes a series of project management recommendations aimed at enhancing project success and sustainability. The novelty of this paper lies in its integration of a comprehensive fuzzy evaluation model that effectively combines multiple evaluation methods, offering a new framework for post-evaluation of complex projects. By merging expert scoring with empirical data, this paper establishes a more objective and comprehensive evaluation system that meets the multidimensional assessment needs of complex projects. The paper not only provides empirical support for 500 kV power transmission and substation projects but also offers a valuable theoretical foundation and practical guidance for decision-makers in the power engineering sector for future project evaluation and management.